Trend Analysis of the Impact of Maternal Health Management on Child Health - Tan, Wenshan; Xiao, Mimi (International Journal of Public Health and Medical Research, 2026)
To evaluate the impact of China's 2009 maternal health management program on service utilization and child health, and examine their association. Using 1998-2020 national time-series data, interrupted time series regression analyzed changes in four maternal service indicators and four child mortality indicators post-implementation. Pearson correlation assessed service-mortality associations. All maternal services showed significant immediate increases post-2009 (systematic management: B=5.53, p